(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
The seminal stains recovered on fabrics are one of the most important evidence in rape cases. Stained clothing’s, undergarments and swab’s on fabric material taken from vagina and surrounding regions, are submitted for DNA Fingerprinting test to compare it with the blood sample of the accused person. Many a times, isolation of DNA from such stains particularly when the stains are old is not possible. The causes could be degradation or decomposition of the biological material, which depends mainly upon the environmental conditions. The other possible factors could be nature of clothing’s. In the present study, it was observed that maximum DNA recovery was from cotton clothing’s even when stored for long durations followed by tricot material.